ASSESSMENT OF PARTICULATE MATTER 10µM (PM10) TRENDS IN TRONOH - MUHAMAD JANI, MUHAMAD AFIQ (Universiti Teknologi PETRONAS, 2017)
PM10 is one of the major pollutant that can contribute significant effect towards the health and environment and usually related with the high particulate event in Malaysia. There were complaints regarding the air quality issue in Tronoh area where the air was seen in hazy condition at which may involve PM10. From initial investigation, the source of emission of PM10 may cause by the traffic, industrial and human activities. The objective of this study is to investigate the trends of PM10 with the development status and to compare the concentration of PM10 with the meteorological parameters such as temperature and humidity. Air monitoring was carried out by using Aeroqual AQM60 which was placed at 3 locations within 2km radius from flyover in Tronoh for 1 weekday and 1 weekend at each location. Based on the 12 hours sampling, the highest average concentration of PM10 recorded is 42.28µg/m3 . The calculation was done to compare the average concentration of PM10 with air pollution index (API). The results show the index of 42.28 which is below 50 which means the environment is still in good condition. The results also show that temperature and humidity affect the concentration of PM10. The study achieved its objective and should be continued further to improve the air quality in Tronoh.